Francophonie en Afrique subsaharienne: dépendance postcoloniale ou autodétermination ? - Dirk Kohnert (Zenodo, 2022)
Africa is today the most important part of the Francophonie. French is an official or co-official language along with other languages in 21 African countries, all in sub-Saharan Africa (SSA). Since the end of colonialism and Cold War politics, changes in the Francophonie have been driven largely by external factors, such as a drive to combat Anglo-American cultural hegemony. Continuities, on the other hand, are mainly due to France's historical affinity with Africa, its view of its place in the world and its understanding of the role of the state. The International Organization of Francophonie (OIF) defends the common interests of the Francophone area and imposes a common vision for reform, particularly in the area of terms of trade. However, the demographic future of Francophonie will play out more and more in southern countries, especially in Africa. In 2010, half of all Francophones worldwide lived in Africa. It is expected that by 2060 almost 84 % of the French-speaking population will live in Africa. Francophonie is mainly driven by the Francophone power elite in, both France and Africa, and the infamous Françafrique patronage network. Both propagate the universality of French as a language, including Pidgin French (often biasedly referred to as `petit-nègre'), culture and way of life. Although the fate of African Francophonie is still determined by the North, the high mobility of the African population, driven by increasing urbanization, means that multilingualism, e.g. the simultaneous use of French and African languages, is 'deterritorialized'. Therefore, it would be crucial to solve the problem of the interface between French and African languages and to identify which other languages could replace French and in which areas this would be most desirable. Apart from that, there are promising perspectives for a self-determined development in the area of the francophone culture of the SSA. The African film industry, literature and religion could make it possible to find a new African rationality, a new way of defining oneself and hoping for a better future, free from the socio-economic inequalities that characterize the francophone post-colony despite globalization. Thus, a viable, dynamic and truly African culture in Francophone SSA could equal and even surpass the rival `Commonwealth culture'. Although both European colonial powers, Great Britain and France, conquered substantial geographic spaces in SSA, using language as a means of control, the resulting networks, the Commonwealth and Francophonie are quite different. – – L'Afrique est aujourd'hui la partie la plus importante de la Francophonie. Le français est une langue officielle ou co-officielle avec d'autres langues dans 21 pays africains, tous en Afrique subsaharienne (ASS). Depuis la fin du colonialisme et de la politique de la guerre froide, les changements dans la francophonie ont été largement motivés par des facteurs externes, tels que la volonté de combattre l'hégémonie culturelle anglo-américaine. Les continuités, en revanche, tiennent principalement à l'affinité historique de la France avec l'Afrique, à sa vision de sa place dans le monde et à sa compréhension du rôle de l'État. L'Organisation internationale de la francophonie (OIF) défend les intérêts communs de l'espace francophone et impose une vision commune des réformes, notamment dans le domaine des conditions commerciales. Or, l'avenir démographique de la Francophonie se jouera de plus en plus dans les pays du Sud, notamment en Afrique. En 2010, la moitié des francophones du monde vivaient en Afrique. Il est prévu que d'ici 2060 près de 84% de la population francophone vivra en Afrique. La francophonie est principalement dirigée par l'élite francophone au pouvoir en France et en Afrique et par le tristement célèbre réseau Françafrique. Tous deux propagent l'universalité du français en tant que langue, y compris le pidgin français (appelé souvent de manière biaisée « petit-nègre »), la culture et le mode de vie. Bien que le sort de la francophonie africaine soit toujours déterminé par le nord, la forte mobilité de la population africaine, entraînée par une urbanisation croissante, signifie que le multilinguisme, par ex. l'usage simultané du français et des langues africaines, est « déterritorialisé ». Il serait donc crucial de résoudre le problème de l'interface entre le français et les langues africaines et d'identifier quelles autres langues pourraient remplacer le français et dans quels domaines cela serait le plus souhaitable. En dehors de cela, il existe des perspectives prometteuses pour un développement autodéterminé dans le domaine de la culture francophone de l'ASS. Le cinéma, la littérature et la religion africaine pourraient permettre de trouver une nouvelle rationalité africaine, une nouvelle façon de se définir et d'espérer un avenir meilleur, libéré des inégalités socio-économiques qui caractérisent la post-colonie francophone malgré la mondialisation. Ainsi, une culture viable, dynamique et véritablement africaine en ASS francophone pourrait égaler et même surpasser la culture rivale du Commonwealth. Bien que les deux puissances coloniales européennes, la Grande-Bretagne et la France, aient conquis de grands empires coloniaux en ASS en utilisant la langue comme moyen de contrôle, les réseaux résultants, le Commonwealth et la Francophonie, sont assez différents.
Additional information: French version of: Kohnert, Dirk (2022): Francophonie in sub-Saharan Africa: Post-colonial dependence or self-determination ?
Keywords: D72; E26; F35; I25; J11; N47; O17; P47; 330; Afrique francophone; Francophonie; Françafrique; franc CFA; union douanière; gouvernance